2004
DOI: 10.1177/0898264303262639
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic and Internal Validity Issues in Sampling in Caregiver Studies

Abstract: Regardless of sampling frame, standard task-based inclusion criteria to define caregivers may enhance validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…This sample was identified in two phases, described in detail elsewhere (Fredman et al, 2004). The first phase consisted of administering a caregiver screening questionnaire to 5,952 SOF participants who had their sixth biennial examination at their home or a SOF clinic and were not cognitively impaired or living in a long-term care facility.…”
Section: Methodsmentioning
confidence: 99%
“…This sample was identified in two phases, described in detail elsewhere (Fredman et al, 2004). The first phase consisted of administering a caregiver screening questionnaire to 5,952 SOF participants who had their sixth biennial examination at their home or a SOF clinic and were not cognitively impaired or living in a long-term care facility.…”
Section: Methodsmentioning
confidence: 99%
“…The large number of black and male respondents allowed us to compare associations across race-gender subgroups. Moreover, in contrast to most studies of caregivers which are based on registries or convenience samples 43 , the Health ABC sample constitutes a population-based sample of community-dwelling adults. Thus, the results are not likely to be biased by the types of caregivers who would volunteer for studies, and are generalizable to community-dwelling adults in their seventies.…”
Section: Discussionmentioning
confidence: 99%
“…17 SOF is a prospective cohort study of risk factors for fractures and falls among women.SOF included 9,704 women aged 65 and older recruited between 1986 and 1988 from population-based listings in four areas of the United States: Baltimore, Maryland; Minneapolis, Minnesota; Portland, Oregon; and the Monongahela Valley, Pennsylvania. 18 Women were excluded if they were unable to walk without help or had a history of bilateral hip replacement.…”
Section: Methodsmentioning
confidence: 99%
“…The study sample was identified in two phases, described in detail elsewhere. 17 The first phase consisted of administering a caregiver screening questionnaire to community-dwelling participants who had their 6th biennial examination and were not cognitively impaired. The second phase began in 1999, and consisted of re-administering the screening questionnaire by telephone to all participants who had been identified by the initial screening questionnaire as caregivers and to a subset of participants who had been identified as non-caregivers.…”
Section: Methodsmentioning
confidence: 99%